Understanding consumers’ behavior intentions towards dealing with the plastic waste: Perspective of a developing country - Khan, Farhana; Ahmed, Waqar; Najmi, Arsalan (Elsevier, 2019)
Plastic consumption has been increasing globally, creating large amount of litter and posing threat to the environment. The recycling of the plastic waste can help in reducing it and its environmental threat. The purpose of this paper is to identify the factors that influence the consumer's return/recycling intention regarding plastic waste. Moreover, recycling behavior of consumer was explored in detail. The theory of planned behavior was adapted and extended to measure the determinants of recycling behavior. Survey research design was employed whereas data includes valid 243 households, collected through survey questionnaire, by employing purposive sampling. PLS-SEM was applied on the collected data for hypotheses testing. The finding of this study indicates that subjective norms, awareness consequences and convenience are major predictors of return/recycling intention. Whereas, hypothesis for the attitude, perceived behavioral control and moral norms were rejected and they all have insignificant impact on return/recycling intention. Moreover, return intention have positive significant impact on resell, reuse, dispose and donate. Reuse was the most predicted by the return intention. This study enriches the literature of reverse logistics helping to understand the consumers’ perspective. Provides the insights that will help government and organizations to understand consumers’ return/recycling intention and formulate such strategies that will increase the involvement of consumers in recycling activities.